From The Manifestation of Speech to Universality (Morphology), From Fundamental Nature to Practical Application (Syntax) - Kavilova Laura (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article examines how parts of speech are classified in French and Uzbek languages from a comparative standpoint. While In French verbal inflection, the stems convey lexical meaning, while the inflectional suffixes trigger functional information based on morphosyntactic features, Uzbek classification primarily considers the logical-semantic features of words due to the absence of inflections in the language. Our study delved into the morphological breakdown and processing of inflectional suffixes using visual lexical decision tasks.